Perlindungan Data Pribadi dalam Perspektif Hukum Perdata: Urgensi, Tantangan, dan Prospek Pengaturan di Indonesia - Paramita, Mahardina Pradnya; Devitasari, Astrid; Kusumasari, Prosawita Ririh (JATIJAJAR LAW REVIEW, 2025)
Digital transformation has created significant opportunities in supporting societal activities; however, it also poses serious threats to data security and personal data protection. Indonesia has faced various data breach cases that reveal the weaknesses of the legal system in providing effective protection. Normatively, the Indonesian Civil Code (KUHPerdata) does not explicitly regulate personal data, while a new regulatory framework was only introduced through Law Number 27 of 2022 on Personal Data Protection (PDP Law). This research aims to analyze personal data protection from a civil law perspective, examine the challenges in implementing the PDP Law, and assess the relevance of classical civil law principles within the digital context. The research employs a normative legal method with statutory, conceptual, and comparative approaches. The findings indicate that personal data protection still encounters obstacles such as low public awareness, limited legal infrastructure, and conflicting interests among the state, corporations, and individuals. Therefore, strengthening civil law instruments to be more adaptive, ensuring consistent implementation of the PDP Law, and renewing civil law doctrines are necessary to remain relevant to the dynamics of digital technology.